Plasmonic lithography for the fabrication of surface nanostructures with a feature size down to 9 nm. Issue 4 (21st November 2019) - Gao, Ping; Pu, Mingbo; Ma, Xiaoliang; Li, Xiong; Guo, Yinghui; Wang, Changtao; Zhao, Zeyu; Luo, Xiangang
Abstract : Aiming to further improve the resolution and quality of plasmonic lithography, a self-aligned patterning technique is introduced to it to obtain ultrafine nanopatterns with high contrast and low LER. Abstract : Aiming to further improve the resolution and quality of plasmonic lithography, a self-aligned patterning technique is introduced to it to obtain ultrafine nanopatterns with high contrast and low line edge error (LER). By improving the line edge roughness of the initial plasmonic lithography patterns, 16 nm half-pitch surface nanostructures with a height of 70 nm can be obtained. Moreover, with the help of plasma etching and atomic layer deposition in this process flow, the LER of the 16 nm half-pitch surface nanostructure can achieve 1.3 nm. Further application indicates that this process can also be used to fabricate nanoholes with the feature size as small as 9 nm. This approach provides a new perspective on the manufacture of surface nanostructures with ultrahigh resolution and high aspect ratios, which would find potentially promising applications in metal–air transistors, biosensors, DNA sequencing, etc .